1887 N.M. Laws 55, ch. 30, § 1 - (:unkn) unknown (General Publisher, 1887)
That any person who shall hereafter carry a deadly weapon, either concealed or otherwise, on or about the settlements of this territory, except it be in his or her residence, or on his or her landed estate, and in the lawful defense of his or her person, family or property, the same being then and there threatened with danger, or except such carrying be done by legal authority, upon conviction thereof shall be punished by a fine of not less than fifty dollars, nor more than three hundred, or by imprisonment not less than sixty days, nor more than six months, or by both such fine and imprisonment, in the discretion of the court or jury trying the same.
--
Keywords: CARRY